Winter cover crops as reservoirs of tobacco rattle virus (TRV) and hosts of root-lesion, root knot and stubby-root nematodes. Issue 4 (4th July 2021) - Elmhirst, Janice F.; Forge, Thomas A.
Abstract: A greenhouse pot study was conducted on four cover crops (annual ryegrass, perennial tetraploid ryegrass, winter wheat cv. 'Caledonia' and sorghum-sudangrass) and one rotation crop (sweet corn cv. 'Sheba') to compare the efficiency of these crop species as hosts of Paratrichodorus minor (Colbran) Siddiqi, and the ability of the nematodes to acquire tobacco rattle virus (TRV) from roots of infected plants and re-transmit it to healthy plants. P. minor reproduced rapidly on sorghum-sudangrass and sweet corn and re-transmitted the virus to indicator plants. Annual ryegrass, perennial ryegrass, and winter wheat cv. 'Caledonia', all of which re-transmitted TRV poorly in the greenhouse, were evaluated in two years of field studies for fall establishment and soil coverage, nutrient sequestration, effect on parasitic nematode populations and on subsequent potato crops. Annual ryegrass performed best overall in terms of establishment, ground cover, overwintering survival and foliar biomass production. None of the cover crops had a consistently significant effect on populations of parasitic nematodes in field plots, including Pratylenchus, Paratrichodorus, and Meloidogyne . Both ryegrass cover crops appeared to provide a favourable environment for survival of root knot nematodes ( Meloidogyne spp.), although they are not considered to be hosts of this nematode. There was no difference in soil carbon, nitrogen or potato yield following any cover crop. Symptoms of corky ringspot were not observed in the field and TRV was not detected in potato plants by RT-PCR.